Analysis of safety and efficacy of conservative treatment and endovascular treatment in patients with spontaneous isolated mesenteric artery dissection - Chen, Xiaobin; Xu, Lei; Xu, Zhaojun; Fan, Zuyou; Huang, Jianqiang; Li, Junjie; Zhang, ZaiZhong; Lin, Chen (Frontiers in Surgery, 2023)
Background Spontaneous isolated superior mesenteric artery dissection (SISMAD) is a rare disease with abdominal pain as the main clinical manifestation, but its optimal treatment strategy has not yet been determined. Based on this, this study explored a safe and effective treatment method by analyzing and comparing the safety and efficacy of conservative treatment and endovascular treatment in SISMAD patients. Methods The clinical and imaging data and treatment effects of 85 patients with SISMAD who were admitted to the General Surgery Department of the 900th Hospital of the Joint Logistics Support Force of the Chinese People's Liberation Army from January 2008 to December 2020 were retrospectively analyzed. Two groups were treated, the data of patients in conservative treatment group and endovascular treatment group were analyzed, and a safe and effective treatment method for SISMAD was discussed. Results The mean follow-up time was 36.58 ± 25.03 months. The success rate of interventional operation was 86.11% (31/36), and the operation failed because the guide wire could not enter the true lumen in four cases. One case was terminated due to poor physical condition of the patient who could not tolerate surgery. There were no significant differences in gender, body mass index, clinical manifestations, and past history between conservative treatment and endovascular treatment (P > 0.05), but in age, superior mesenteric artery-distal aorta angle, distance from the superior mesenteric artery opening to dissection, dissection length, and true lumen stenosis. There was a statistical difference between the two groups in the rate and Yun classification (P < 0.05). Conclusions Conservative treatment is effective for most symptomatic SISMAD patients, and close monitoring is required; for patients with persistent symptoms and severe true lumen stenosis (especially Yun classification type III), endovascular treatment is preferred; endovascular treatment is mainly based on endovascular bare stent placement. Patients receiving stent implantation may suffer from stent stenosis or occlusion in the long term, and most of them have no obvious symptoms of intestinal ischemia; the prognosis is good.